Multi-faceted approaches and interdisciplinary narratives – regional archaeologies in Akarnania and Olympia (Western Greece) - Lang, Franziska (Journal of Greek Archaeology, 2019)
Landscape is a multi-agent-system in which the agent ‘Landscape’ with its natural-spatial conditions causes and is subjected to changes through natural processes and events (such as natural disasters). On the other hand, landscape is transformed through human agents appropriating it by intentional and reflective actions (Werlen 2010b: 9–17).